2015
DOI: 10.1111/nph.13306
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effects of extracellular self‐DNA: a general biological process?

Abstract: SummarySelf-inhibition of growth has been observed in different organisms, but an underlying common mechanism has not been proposed so far. Recently, extracellular DNA (exDNA) has been reported as species-specific growth inhibitor in plants and proposed as an explanation of negative plant-soil feedback. In this work the effect of exDNA was tested on different species to assess the occurrence of such inhibition in organisms other than plants.Bioassays were performed on six species of different taxonomic groups,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
108
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 100 publications
(125 citation statements)
references
References 47 publications
8
108
1
1
Order By: Relevance
“…When damaged plant cells release DNA it can be further metabolized to produce DNA fragments in a variable size range (usually between 50 and 2000 bp (base pair)). It has been recently argued that this extracellular fragmented self-DNA (esDNA) acts as a signaling molecule (or second messenger) able to trigger inhibitory effects on conspecific plants [1,2,3]. Moreover, plants use this esDNA to build resistance against pathogens and as a means of maintaining biodiversity [4].…”
Section: Introductionmentioning
confidence: 99%
“…When damaged plant cells release DNA it can be further metabolized to produce DNA fragments in a variable size range (usually between 50 and 2000 bp (base pair)). It has been recently argued that this extracellular fragmented self-DNA (esDNA) acts as a signaling molecule (or second messenger) able to trigger inhibitory effects on conspecific plants [1,2,3]. Moreover, plants use this esDNA to build resistance against pathogens and as a means of maintaining biodiversity [4].…”
Section: Introductionmentioning
confidence: 99%
“…Their results indicate a general occurrence of litter autotoxicity related to the exposure to fragmented extracellular DNA. Hence, while the effects of negative plant-soil feedback on the spatial structure of individual plants depend on the intensity of the underlying density-dependent mechanisms (Bagchi et al 2010), its ubiquitous presence suggests that plant-soil feedback may play an important role in the maintenance of plant diversity in natural (cm) communities (Mazzoleni et al 2015b). In a review on direct evidences on conspecific negative plant-soil feedback from both terrestrial and aquatic plants, Mazzoleni et al (2007) reported 138 cases of conspecific negative plant-substrate interactions, 96 of which are associated with grassland species, including Erigeron canadensis, one species of Veronica and one species of Viola, thus reinforcing the hypothesis that plant-soil feedbacks may contribute to the disruption of shortrange phylogenetic clustering (see also Anacker et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In this view, the spatial aggregation of conspecifics induced by local dispersal needs to be disrupted to some extent by mechanisms increasing within-species segregation, like distance-or density-dependent mortality (Chesson 2000). Such inverse relationship between local conspecific density and individual performance has been related to the activity of host-specific insects or fungi (Janzen 1970, Connell 1971, the build-up of negative plant-soil feedback due to the accumulation of species-specific soil-borne pathogens Clay 2000, van der Putten et al 1993), the changing composition of soil microbial communities (Bever 1994, Klironomos 2002, or the release of autotoxic compounds from decaying litter (Singh et al 1999, Mazzoleni et al 2015a, 2015b. All these mechanisms, which are linked to the physical and chemical properties of plants rather than to their functional characters, will locally increase species diversity by reducing the chance of conspecific juveniles to colonize sites close to adult individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Soils are involved in the transmission of genetic information within each natural ecosystem (Cartenì et al, 2016;Mazzoleni et al, 2015aMazzoleni et al, , 2015bLevy-Booth et al, 2007;Pietramellara et al, 2009;Nielsen et al, 2007Nielsen et al, , 2015. In given areas of our planet, plants and animals coevolve.…”
Section: Is Soil Involved In the Process Of Natural Evolution?mentioning
confidence: 99%
“…Recent studies show that even plants are able to uptake DNA fragments and that the process could be related to the plant biodiversity in planetary biomes (Mazzoleni et al, 2015a(Mazzoleni et al, , 2015b. A small fragment of DNA generated in a litter is able to enter a host cell, recognize inside its homologous genomic target and activate the machinery involved in DNA repair with the consequent integration into the genomic DNA of the host cell (reviewed by Cartenì et al, 2016).…”
Section: Is Soil Involved In the Process Of Natural Evolution?mentioning
confidence: 99%